KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 3 LEMBAH GUMANTI KABUPATEN SOLOK DENGAN STRATEGI PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES REVIEW - Husna, Asmaul (, PRODI. MATEMATIKA, RIAU KEPULAUAN UNIVERSITY, BATAM, INDONESIA, 2016)
Abstract. This study aims to prove: 1) Is the concept comprehension capabilities of class VII SMP N 3 Lembah Gumanti in mathematics learning using active learning strategies type of Hollywood Squares Review is better than using conventional learning, 2) How does the achievement indicator of the concept comprehension capabilities of class VII SMPN 3 Lembah Gumanti in mathematics learning using active learning strategies and the type of Hollywood Squares Review using conventional learning. The population in this study was students of class VII SMP N 3 Lembah Gumanti while the sample was the VII 1 students of SMP N 3 Lembah Gumanti as experiment class and Â the VII 2 students of SMP N 3 Lembah Gumanti as the control class that choosen randomly. The instrument used was a written test. Data were analyzed using one tailed t-test. Based on the data analysis, the statistical significance value = 0.000 less than the significance level (Î± = 0.05) means that H0 was rejected or the concept comprehension capabilities of students who use active learning strategies type of Hollywood Squares Review was better than the students who use conventional learning.Keywords: active learning strategies type of Hollywood Squares Review, concept comprehension capabilities